ALTERNATIVE JUSTICE MECHANISMS AS A DAILY JUSTICE POLICY IN THE FACE OF THE CONFLICT OVER THE USE OF WATER IN MEXICO AND ITS POTENTIAL APPLICATION IN PERU - Sánchez Garcia, Arnulfo (2019)
The two main countries producers of silver ore in the world, Mexico and Peru, share a situation of disparity in the availability of water by regions, together with the conflict generated by their mining operations. silver is the element that shows the similarity between the study spaces of this work, the main regions with the highest volume of silver production in both countries, the State of Zacatecas and the department of Junín, have been selected to analyze the existing problems due to the use of water resources between mining companies and adjacent populations, and how the intervention of alternative justice mechanisms can be materialized in a daily justice policy that resolves these conflicts.